THE ROLE OF THE SCHOOL PRINCIPLE IN IMPROVING THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS AND IN THE PANDEMI PERIOD - Abdul Malik (Universitas Islam Negeri Mataram, 2023)
This article seeks to explain the role of school principals in improving elementary school teacher performance and parental involvement during the pandemic. So far, the pandemic has changed and changed the established academic culture. One of the academic cultures that has undergone many changes and transformations is the role of the principal, the performance of teachers and the involvement of student guardians in elementary schools. Therefore, this research was conducted through a qualitative method in which the researcher became the key tool in extracting data using in-depth interviews and observational techniques. The results of this study indicate that in order to maintain the quality of teacher performance, principals often hold training or similar activities to improve teacher performance by involving all existing teachers. At the same time involving the intervention and participation of student guardians, student guardians intervene via social media such as the WA group to participate in learning assessments in the form of providing input and support for school and student progress